A survey of facilitators and barriers to recruitment to the MAGNETIC trial. Issue 1 (December 2016) - Kaur, Geetinder; Smyth, Rosalind; Powell, Colin; Williamson, Paula
Abstract Background Recruitment to randomised controlled trials with children is challenging. It is imperative to understand the factors that boost or hinder recruitment of children to clinical trials. We conducted a survey of facilitators and barriers to recruitment to the MAGNETIC trial, using a previously developed web-based tool. Methods MAGNETIC is a multicentre randomised trial of nebulised magnesium in acute severe asthma, recruiting 508 children from 30 UK sites. Recruiters were asked to grade a list of factors from –3 to +3 depending on whether the factor was perceived as a strong, intermediate or weak barrier (–3 to –1) or facilitator (+1 to + 3), and using (0) if it was thought to be not applicable. Free text responses were invited on strategies applied to counter the identified barriers. Results The commonly identified facilitators were motivation and experience of study teams, effective communication and coordination between teams at site and between sites and the Clinical Trials Unit, the presence of designated research nurses, good trial management, clinical trial publicity, simple inclusion criteria, effective communication with parents and presentation of trial information in a simple and clear manner. The commonly identified barriers were heavy clinical workload, shift patterns of work, Good Clinical Practice (GCP) training, inadequate number of trained staff, time and setting of consent seeking, non-availability of research staff out of hours and parents' concerns about their child taking an experimental medicine. Having a designated research nurse, arranging GCP training and trial-related training sessions for staff were the most commonly reported interventions. Conclusions This study highlights important generic and trial-specific facilitators and barriers to recruitment to a paediatric trial in the acute setting and provides information on the recruitment strategies or interventions that were applied to overcome these barriers. This information can be very useful in informing the design and conduct of future clinical trials with children, particularly in the acute or emergency setting. Trial registration ISRCTN, ISRCTN81456894 . Registered on 15 November 2007.